Thermal Analysis of Power Cables Using Finite Element Method and Current-carrying Capacity Evaluation - (:unkn) unknown (TEMPUS PUBLICATIONS, 2009)
For engineering education students, solution of an electric-thermal multiphysics problem by using COMSOL program which is based on finite element method has been presented. In considering the problem, the current-carrying capacity and heat distribution of power cables buried in soil were determined depending on the thermal conductivity of the surrounding soil and different buried depths, from the temperature distribution calculations using COMSOL (FEMLAB). The electrical losses due to the current flowing in the cable conductor and electric field which heats up the cable was taken into consideration in the heat conduction equation, to accommodate the electrical losses in calculating the current-carrying capacity. The results show that the current-carrying capacity of the cable with increasing conductivity is increased and wind velocity has a low influence on the current-carrying capacity. Also humidity content in insulating material has an important effect on increase in the temperature of power cables because of increasing insulation conductivity after a certain temperature.
Keywords: power cable; thermal analysis; FEM; multiphysics analysis; COMSOL; NUMERICAL TECHNIQUES